1998
DOI: 10.7326/0003-4819-128-6-199803150-00002
|View full text |Cite
|
Sign up to set email alerts
|

Unfavorable Effects of Passive Smoking on Aortic Function in Men

Abstract: Both passive and active smoking are associated with an acute deterioration in the elastic properties of the aorta. This association between exposure to tobacco smoke and aortic elasticity indicates that aortic function deteriorates during passive or active smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0
26

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(114 citation statements)
references
References 38 publications
4
82
0
26
Order By: Relevance
“…32 Passive smoking Three different studies found that exposure to environmental tobacco smoke (ETS) for 5-60 min leads to increased arterial stiffness (Table 3). 34,55,56 However, in one study, this change was noted only in male subjects. 56 No change was observed after exposure to nontobacco smoke in any of the studies.…”
Section: Chronic Smokingmentioning
confidence: 95%
See 1 more Smart Citation
“…32 Passive smoking Three different studies found that exposure to environmental tobacco smoke (ETS) for 5-60 min leads to increased arterial stiffness (Table 3). 34,55,56 However, in one study, this change was noted only in male subjects. 56 No change was observed after exposure to nontobacco smoke in any of the studies.…”
Section: Chronic Smokingmentioning
confidence: 95%
“…[29][30][31][32][33][34] Swampillai et al 35 reported a significant smoking-induced increase in stiffness index (SI) 15 min after smoking (Po0.05), but did not observe changes in wave speed in the carotid artery.…”
Section: Acute Smokingmentioning
confidence: 99%
“…Table 3 summarizes the main endothelial alterations due to passive smoke exposure. Evidence indicates that chronic exposure to passive smoking causes an increase in arterial stiffness as an effect of repeated and prolonged endothelial dysfunction [43][44] as experimentally documented in the aorta of men.…”
Section: Citationmentioning
confidence: 99%
“…Már egy szál cigaretta által okozott ötpercnyi PD-expozíció a leukocyták endothelsejtekhez való adhézióját károsítja [21]. A dohányzás további adverz, egészségre káros hatásai közül kiemelendő az endothelialis diszfunkcióra való hatás [22,23,24], illetve a gyermekek körében az asthmaexacerbatio is [25].…”
Section: Megbeszélésunclassified